Epilepsy - Czuczwar, Stanislaw J (Exon Publications, 2022)
Epilepsy is a neurological disorder that affects about 65 million people worldwide. Although antiepileptic drugs provide sufficient control of seizures in approximately 70% of patients with epilepsy, the remaining 30% are resistant to monotherapy. This means around 20 million people worldwide face significant adverse life-long consequences such as sudden unexpected death from epileptic seizures, increased risk of injuries, and learning and developmental disabilities at school age. That is why, a continuous search for drugs targeting novel antiseizure mechanisms and alternative ways of epilepsy management is going on. This book covers a number of valid issues aimed at understanding the etiology and pathophysiology of epilepsy, epilepsy genetics, current therapeutic challenges, and possible novel therapeutic targets. The authors point to a number of etiologic factors, which incorporate anatomic, acquired, genetic, metabolic, and immunologic aspects. The overlap between neurodevelopmental disorders and epilepsy, and the involvement of hippocampal sclerosis in the process of epileptogenesis are also elegantly described. The readers will also find a very detailed description of the contemporary management of status epilepticus. There are also clues on how to inhibit a very dangerous super refractory status epilepticus. Regarding precision medicine-based management of epilepsy, recent data on GABAA receptor variants and canonical transient receptor potential channels are provided, which can help develop novel strategies for epilepsy treatment. Ketogenic diet may be considered as a non-pharmacological option for children and adolescents suffering from drug-resistant epilepsy. The book, covering various aspects of epilepsy from receptor and genetic studies to therapeutic clues, will be of particular value to scientists and clinicians.